Kingdom of Lesotho : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission regarding compilation of Government Finance Statistics (GFS) in Lesotho. The IMF mission reviewed current compilation methods of GFS for the budgetary central government and found that there were significant accuracy, classification, coverage, and comprehensiveness issues that undermine the credibility of fiscal statistics currently compiled and disseminated. Currently compiled and disseminated GFS include a large and persistent statistical discrepancy. The statistical discrepancy averaged to about a third of total revenue in preliminary data for FY2016/17 and FY2017/18. The mission also identified and discussed with the staff of the Ministry of Finance a number of reasons that may partly explain the discrepancy.